PENERAPAN TA’ZIR EDUKATIF DALAM MENANAMKAN KEDISIPLINAN PADA SANTRI (STUDI KASUS DI PONDOK PESANTREN FADLILLAH TAMBAK SUMUR WARU SIDOARJO) - Sofyan, Ahmad (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
This research aims to discuss: (1) How is ta'zir implemented at the Fadliliah Tambak Sumur Waru Islamic Boarding School, Sidoarjo?; (2) How does ta'zir at the Fadlillah Tambak Sumur Waru Islamic Boarding School, Sidoarjo, apply discipline to students? This research uses a descriptive qualitative approach. Data collection techniques use interviews, participant observation and documentation. Data analysis consists of data reduction, data presentation and drawing conclusions. Checking the validity of the data is carried out through extended participation, diligent or consistent observation, triangulation and peer checking. The results of this research explain that (1) the Fadlillah Waru Sidoarjo Islamic Boarding School provides disciplinary guidance to students in order to achieve educational goals in the Islamic boarding school environment. This disciplinary action takes the form of giving punishment (ta'zir), for example going bald, destroying the Koran and so on. Disciplinary action against students at the Fadlillah Waru Sidoarjo Islamic boarding school is a way of disciplining boarding school administrators towards problematic students so that they obey the rules that have been set and agreed upon by the management of the boarding school. The application of punishment is also understood as a means of educating students so that it has a deterrent effect and does not repeat it again; (2) Ta'zir is considered an effective method in the process of disciplining students. However, this does not necessarily become the main step in the disciplinary action. Sometimes these actions actually make students feel depressed.